AKIBAT PENGGUNAAN OBAT ANTIHIPERTENSI PORTAL TERHADAP EPISODE KEJADIAN HEMATEMESIS-MELENA PADA PASIEN DENGAN SIROSIS HATI DI RSUP Dr SARDJITO YOGYAKARTA - , Eka Purnomo, Prof. Dr. Djoko Wahyono, SU., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background : Hematemesis and/or melena are complaints frequently occurring in patients with heart sirosis with varicose veins of gastroesophagous. Hematemesis and/or melena occur because there is varicose vein bleeding. Each bleeding episode brings mortality rate ranged from 25% to 30%. Prevention of varicose vein bleeding using appropriate portal anti-hypertensive medicine may minimize mortality risk. Purpose : This research aimed to understand profile of use of portal antihypertension and evaluate use of portal anti-hypertensive medicine consisting of: exact dosage and therapy outcome. Method : This research is observational-descriptive study and it was conducted retrospectively. Subjects of research were patients of RSPU Dr. Sardjito Yogyakarta receiving portal anti-hypertensive medicine from January of 2008 to December of 2010. Collectable data were reviewed and discussed by references of most recent guidelines. Result : 41 inclusive cases indicated that 92.7% of patients used propranolol and 7.3% of patients used isosorbid mononitrate. Given outcome of use of portal antihypertensive medicine based on hematemesis and/or melena incidences in patients using propranolol as primary prophylaxis, one patient (11.1%) experienced hematemesis, while, in patients using isosorbid mononitrate, it could prevent incidence of hematesis and/or melena. In patients using propranolol as secondary prophylaxis, 11 patients (37.9%) experienced hemetemesis and/or melena, while in patients using isosorbid mononitrate, it could not prevent incidence of hematesis and/or melena. Conclusion : In propranolol secondary prophylaxis, there were 9 patients using propranolol and one patient using isosorbid mononitrate. Based on achievable responses, there was one patient experiencing hematemesis. It was caused by non optimum propranolol dosage. While one patient using isosorbid mononitrate could prevent hematemesis and/or melena in patients with liver Cirrhosis. In secondary prophylaxis, there were 29 patients using propranolol and two patients using isosorbid mononitrate. Based on achievable responses, there were 11 patients using propranolol experiencing hematemesis and/or melena. It was caused by non optimum propranolol dosage and there was one patient using propranolol experiencing hematemesis and/or melena.